Impact of inter‐ and intra‐specific competition among larvae on larval, adult, and life‐table traits of Aedes aegypti and Aedes albopictus females. (8th December 2015) - NODEN, BRUCE H.; O'NEAL, PAUL A.; FADER, JOSEPH E.; JULIANO, STEVEN A.
Abstract : 1. Few studies have taken a comprehensive approach of measuring the impact of inter‐ and intra‐specific larval competition on adult mosquito traits. In this study, the impact of competition among Aedes aegypti (L.) and A. albopictus (Skuse) was quantified over the entire life of a cohort. 2. Competitive treatments affected hatch‐to‐adult survivorship and the development time to adulthood of females for both species but affected the median wing length of females only for A. albopictus . Competitive treatments had no significant effect on the median adult female longevity nor were there any effects on other individual traits related to blood feeding and reproductive success. 3. Analysis of life table traits revealed no effect of competitive treatment on the net reproductive rate ( R 0 ) but there were significant effects on the cohort generation time ( T c ) and the cohort rate of increase ( r ) for both species. 4. Inter‐ and intra‐specific competition among Aedes larvae may produce individual and population‐level effects that are manifest in adults; however, benign conditions may enable resulting adults to compensate for some impacts of competition, particularly those affecting blood‐feeding success, fecundity, and the net reproductive rate, R 0 . The effect of competition, therefore, affects primarily larva‐to‐adult survivorship and the larval development time, which in turn impacts the cohort generation time, T c, and ultimately the cohort rate of increase, r . 5. The lack of effects of the larval rearing environment on adult longevity suggests that effects on vectorial capacity owing to longevity may be limited if adults have easy access to sugar and bloodmeals.